Role of fintech in financial inclusion: A quantitative review - Mona Sharma; Jyotika Bahl; Pushpender Gothwal; Dev Kumar; Luxmi Atree; Sunil Kumar (Malikussaleh University, Aceh, Indonesia, 2025)
This study presents a comprehensive bibliometric analysis of the scholarly literature on fintech and financial inclusion. Using a structured search strategy, 611 articles published in Scopus-indexed journals were analysed to uncover key trends, contributors, and research themes within this rapidly evolving field. The analysis identifies “sustainable development” and “China” as well-developed and central motor themes, while “fintech,” “financial inclusion,” and “electronic money” remain central yet still developing areas of inquiry. Notably, Ozili P.K. emerged as the most influential author, with a high citation impact and H-index, followed by Banna H and Mhlanga D. The Journal of Risk and Financial Management, Sustainability (Switzerland), and Finance Research Letters were the leading publication outlets. Geographically, India led in terms of publication volume, reflecting its dynamic fintech ecosystem, whereas the UK and US showed strong international research collaborations. Despite a solid foundation, the literature reveals underdeveloped focus areas, particularly regarding the traditional financial system and the integration of emerging technologies. These points point to meaningful gaps for future exploration, including the application of blockchain, artificial intelligence, and digital identity frameworks to promote inclusive finance. Additionally, socio-cultural factors influencing fintech adoption remain insufficiently explored, especially in underserved communities. Cross-country comparative research and long-term studies are also needed to deepen our understanding of fintech’s role in achieving inclusive and sustainable economic growth.